DISTRIBUSI SEROTIPE DENGUE DI SURABAYA TAHUN 2012 - Aryati, Aryati; Wardhani, Puspa; Yohan, Benediktus; Aksono H, Eduardus Bimo; Sasmono, R. Tedjo (Indonesian Association of Clinical Pathologist and Medical laboratory, 2012)
The characteristics of epidemic dengue often presented as periods of hyperendemicity or as the co-circulation of multiple dengue serotypes. Surabaya is an endemic city for Dengue virus (DENV) transmission. Previous study of DENV distribution in 2008-2009 revealed the predominance of DENV-2. DENV serotypes distribution is known to be dynamic and serotype predominance may change through time. This study aims to determine and follow the circulation of DENV serotype in Surabaya in 2012. We recruited 154 denguesuspected patients attending Dr. Soetomo Hospital during February until August 2012. Dengue cases were confirmed by IgG and IgM serology tests and NS1 antigen detection. Serologically-positive samples were further analyzed using two-steps reverse transcriptasepolymerase chain reaction (RT-PCR) and viruses were isolated by propagation in C6/36 mosquito cell line. Seventy one cases (46.1%) were detected as DENV positive infection. Serotyping revealed that 61 samples have monotypic infection with one of all four of DENV serotypes and 10 samples have mix-infections. Overall serotyping result observed the predominance of DENV-1 (60.56%). Our result revealed the circulation of all four serotypes of DENV and the presence of serotype exchange in Surabaya in 2012. Annual change of predominant serotype and the presence of multiple infections may play an important role in the transmission of dengue infection. This information is valuable to dengue surveillance in the region. Therefore, the laboratory diagnosis of DENV serotype should be routinely performed to follow the dynamic of dengue disease